Foundations of Yoga Psychology - Rao, K. Ramakrishna (SpringerLink Bücher, 2017)
This book discusses the profound philosophy and practical psychology behind yoga, beyond its popular body-culture aspect. It pays particular attention to the psychological principles involved and their implications for the consummate understanding of human nature. It explores the psychological aspects of yoga theory and practice and discusses the aphorisms in Patanjali’s treatise on Yoga with necessary commentary in current psychological terminology to make them intelligible to students of psychology and other interested readers. Importantly, the author draws out the implications of these aphorisms for future psychological study and research. The book discusses the author’s concept of yoga of nonviolence which brings in Gandhian ideas into the framework of yoga. The author’s own vast experience in creating interfaces of yoga research with practice also informs the discussions in this book. This authoritative and topical book by an eminent academic like Professor Ramakr ishna Rao is of interest to scholars and students of diverse disciplines, including but not limited to psychology, philosophy and wellbeing research